From expectation to reality: A study on self-efficacy and motivational adjustment of Indonesian pre-service English teachers in cross- cultural teaching in Thailand - Juthathip Mingkun; Andrea Rinjani Purwanto; Chelvino Dimas Hardita; Legisia Euvania; Concilianus Laos Mbato (Universitas Islam Negeri Ar-Raniry, 2026)
Cross-cultural teaching experiences, while often challenging, offer significant developmental value for pre-service teachers. Participants in such programs frequently encounter cultural norms and instructional contexts that diverge from their prior expectations. Despite the growing prevalence of international teaching practicums, empirical research specifically examining the expectation–reality gap in cross-cultural teaching remains limited. To address this gap, the present study investigates how Indonesian pre-service English teachers experience shifts between their initial expectations and classroom realities during a one-month teaching placement in Chiang Rai, Thailand. In addition, the study explores how such teaching experiences influence the participants' professional confidence and motivation. Employing a qualitative descriptive design, the researchers recruited five participants and conducted semi-structured interviews. The data were analyzed thematically to identify recurring patterns and emergent themes. The findings indicate that participants experienced uncertainty and diminished confidence when confronted with unanticipated classroom events and cultural differences. Over time, however, the cross-cultural environment served as a catalyst for rebuilding both confidence and motivation, suggesting that such challenges can be reframed as opportunities for professional growth within international English language teaching contexts. The study concludes by emphasizing the necessity of preparing pre-service teachers not only in pedagogical skills but also in cultural awareness and adaptability prior to participation in international practicum programs.